2020
DOI: 10.24191/jchs.v5i2.10114
|View full text |Cite
|
Sign up to set email alerts
|

Exploring challenges faced by parents of children with tuberculosis to achieve treatment success

Abstract: Introduction: Parents play an essential role in the success of their children’s tuberculosis (TB) treatment. They faced many challenges from the initial children’s health status changes until completing the TB treatment. The challenges were also described as perceived barriers, according to the Health Belief Model (HBM). This study aims to explore parents’ experiences on the challenges in achieving a successful TB treatment for their child in two districts of Selangor, Malaysia. Methods: The research was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Tuberculosis is associated with death, and it is referred to as the “ghost cough” disease ( nsamanwa ) in a Ghanaian local language (Twi) (Nketiah‐Amponsah et al, 2021). Understandably, a diagnosis of childhood TB contributes to a mother's fear that her child may die (Awaluddin et al, 2020a). It is therefore important that the fears, thoughts and worries of mothers about their children's diagnosis and well‐being are assessed and managed adequately by healthcare providers through appropriate parental involvement, counselling and education (Aarthun et al, 2019; Choudhary & Ahmed, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tuberculosis is associated with death, and it is referred to as the “ghost cough” disease ( nsamanwa ) in a Ghanaian local language (Twi) (Nketiah‐Amponsah et al, 2021). Understandably, a diagnosis of childhood TB contributes to a mother's fear that her child may die (Awaluddin et al, 2020a). It is therefore important that the fears, thoughts and worries of mothers about their children's diagnosis and well‐being are assessed and managed adequately by healthcare providers through appropriate parental involvement, counselling and education (Aarthun et al, 2019; Choudhary & Ahmed, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have explored the experiences of caregivers of children living with TB in settings such as China, Malaysia and Brazil (Awaluddin et al, 2020a;da Silva et al, 2014;Zhang et al, 2014).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there is inadequate evidence on the barriers to identifying and diagnosing childhood TB from caregivers' and providers' perspectives. The existing literature reports only the lack of knowledge [ 13 , 14 ] of caregivers and transportation costs [ 37 ]. A study in Dhaka at the BRAC urban directly observed therapy short course (DOTS) sites reported managerial officials' frequent turnover in government, stigma, care-seeking delay, inadequate diagnostic facilities, and private practitioners’ limited involvement as challenges in the implementation of childhood TB control program [ 38 ].…”
Section: Introductionmentioning
confidence: 99%